Microsatellites for genetic studies and breeding programs in common bean - Campos, Tatiana de; Benchimol, Luciana Lasry; Carbonell, Sérgio Augusto Moraes; Chioratto, Alisson Fernando; Formighieri, Eduardo Fernandes; Souza, Anete Pereira de (Pesquisa Agropecuaria Brasileira, 2007)
Twenty microsatelitte loci were identified and characterized in common bean. Microsatellites were tested in 14 genotypes. The allele number ranged from 1 to 3, and the polymorphism information content (PIC) was between 0.14 and 0.65. These polymorphic markers are available to be used for breeding programs.